2021
DOI: 10.3390/gels7010013
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Crosslinkable Maleimide-Modified Hyaluronic Acid and Gelatin Hydrogel Delivery System for Regenerative Applications

Abstract: Hydrogels have played a significant role in many applications of regenerative medicine and tissue engineering due to their versatile properties in realizing design and functional requirements. However, as bioengineered solutions are translated towards clinical application, new hurdles and subsequent material requirements can arise. For example, in applications such as cell encapsulation, drug delivery, and biofabrication, in a clinical setting, hydrogels benefit from being comprised of natural extracellular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Such polymers have a network which, due to their hydrophilic nature, may absorb large amounts of water [ 6 , 7 , 8 , 9 ] and physiological fluids without dissolving [ 6 , 10 , 11 , 12 ]. The hydrogel network is crosslinked by chemical bond or physical entanglements, which give them the ability to swell or shrink and, in general, alter the overall structure [ 13 , 14 , 15 , 16 , 17 ]. The knowledge and the control at molecular level of a hydrogel structure is then a crucial issue in the network customization to permit the diffusion of a specific target, based on the size and the chemical content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such polymers have a network which, due to their hydrophilic nature, may absorb large amounts of water [ 6 , 7 , 8 , 9 ] and physiological fluids without dissolving [ 6 , 10 , 11 , 12 ]. The hydrogel network is crosslinked by chemical bond or physical entanglements, which give them the ability to swell or shrink and, in general, alter the overall structure [ 13 , 14 , 15 , 16 , 17 ]. The knowledge and the control at molecular level of a hydrogel structure is then a crucial issue in the network customization to permit the diffusion of a specific target, based on the size and the chemical content.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the diffusivity of a solute through a crosslinked hydrogel decreases as crosslinking density increases, as the size of the solute increases and as the volume fraction of water within the gel decreases [ 18 ]. Because of wide application, in the last years, several methods have been developed to study bulk hydrogel properties, both theoretically and experimentally [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…113 Similarly, human dermal fibroblast cultured in maleimide-modified hyaluronic acid and gelatin hydrogels crosslinked with polyethylene glycol have shown continuous proliferation. 114 Accordingly, a 3D structure composed by hyaluronic acid provides greater hydration and a better diffusion of nutrients. Moreover, this polysaccharide not only increases the mechanical properties of the construct such as greater support to compression, tension, and shear loads, but also enhances physicochemical properties such as swelling degree, viscoelasticity and permeability.…”
Section: -(3-dimethylaminopropyl) Carbodiimide Hydrochloride the Resultsmentioning
confidence: 99%
“…In another study, gelatin and hyaluronic acid were crosslinked with different ratios of ethyl‐3‐(3‐dimethylaminopropyl) carbodiimide hydrochloride, the results showed that the hydrogels have no cytotoxicity and promote cell proliferation 113 . Similarly, human dermal fibroblast cultured in maleimide‐modified hyaluronic acid and gelatin hydrogels crosslinked with polyethylene glycol have shown continuous proliferation 114 . Accordingly, a 3D structure composed by hyaluronic acid provides greater hydration and a better diffusion of nutrients.…”
Section: Injectable Hydrogels Used For Hyaline Cartilage Recoverymentioning
confidence: 99%
“…[33] HA was partially functionalized with maleimido groups as reported in literature. [34] To this purpose the carboxylic groups were activated with N-hydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) and condensed with 2-maleimidoethylamine, generating a maleimide-functionalized HA (HAÀ MA) (Scheme 1b). HAÀ MA has been characterized and by 1 H-NMR and FT-IR.…”
Section: Resultsmentioning
confidence: 99%